Effects of fatty acid amide hydrolase (FAAH) inhibitors on working memory in rats - Panlilio, Leigh V. (Psychopharmacology (Berl), 2015)
RATIONALE: Manipulations of the endocannabinoid system could potentially produce therapeutic effects with minimal risk of adverse cannabis-like side effects. Inhibitors of fatty acid amide hydrolase (FAAH) increase endogenous levels of the cannabinoid-receptor agonist, anandamide, and show promise for treating a wide range of disorders. However, their effects on learning and memory have not been fully characterized. OBJECTIVES: We determined the effects of five structurally different FAAH inhibitors in an animal model of working memory known to be sensitive to impairment by delta-9 tetrahydrocannabinol (THC). METHODS: A delayed nonmatching-to-position procedure was used in rats. Illuminated nosepoke holes were used to provide sample cues (left versus right) and record responses (correct versus incorrect) after delays ranging from 0-28 seconds. Various test drugs were given acutely up to two times per week before daily sessions. RESULTS: One FAAH inhibitor, AM3506 (3 mg/kg), decreased accuracy in the memory task. Four other FAAH inhibitors (URB597, URB694, PF-04457845, and ARN14633) and a monoacylglycerol lipase inhibitor (JZL184, which blocks the degradation of the endocannabinoid 2-arachidonoylglycerol) had no effect. Testing of AM3506 in combination with antagonists for receptors known to be affected by anandamide and other fatty-acid amides indicated that the impairment induced by AM3506 was mediated by cannabinoid CB(1) receptors, and not by alpha-type peroxisome proliferator-activated receptors (PPAR-alpha) or vanilloid transient receptor potential cation channels (TRPV1). CONCLUSIONS: FAAH inhibitors differ with respect to their potential for memory impairment, abuse liability, and probably other cannabis-like effects, and they should be evaluated individually for specific therapeutic and adverse effects.